Efeito neuroprotetor do óleo de abacate (Persea americana) em um modelo in vitro de estresse induzido por cortisol - Motta, Jéssica de Rosso (2020)
Introduction: Aging brings with it concerns specific to age, with the physiological decline, the onset or worsening of diseases, including psychiatric disorders such as depression, physical and psychological changes related to advancing age. Stress has been described by many authors as a possible trigger for the development of a series of psychiatric and metabolic pathologies and the hormone cortisol at high levels seems to be the link between stress and the development of dysfunctions, including neuronal degeneration and death. Given this context and taking into account that the elderly population in most cases makes use of a large amount of drugs, the search for nutritional elements that can contribute to the fight against stress is justified. One nutritional element to be considered is omega 3, present in a considerable concentration in avocado (Persea americana), a fruit widely distributed and consumed in all regions of Brazil. Objective: to evaluate the neuroprotective effect of avocado oil (Persea americana) in an in vitro model of stress induced by cortisol. Methodology: SHSY-5Y neuronal cells were treated with avocado oil, obtained commercially, in the concentrations of (2, 5, 10, 20 and 30 μg / mL) during 24 hours of incubation. A concentration-response curve was also performed with cortisol, obtained commercially via Sigma Aldrich (0.1, 0.3, 1, 3, 10ng / mL). Once the concentrations were determined, new experiments were carried out where neural cells were simultaneously exposed to cortisol and avocado oil in order to measure markers related to oxidative stress, apoptosis, BDNF neurogenic protein levels and antioxidant levels. Results: Exposure to cortisol alone significantly reduced cell viability (except 0.1 ng / mL). On the other hand, neural cells exposed to different concentrations of avocado oil showed similar viability to the control group. 10µg / mL of avocado oil and 1ng / mL of cortisol were defined as the doses of choice for the next steps. A significant increase in the levels of antioxidant enzymes was observed in all treatments. All the oxidative markers analyzed, were reduced when the presence of avocado oil was made concomitantly with cortisol. Apoptotic markers such as caspases 3 and 8 had a decrease in the presence of avocado oil, and there was an increase in BDNF levels, when compared with the numbers of cortisol alone. Discussion: In general, concomitant treatment with cortisol and avocado oil reversed the damage caused by cortisol to neurons, indicating the relevance of the tested molecule as a possible neuroprotective in the face of chronic stress which is closely related to high levels of cortisol. Conclusion: Our results showed an important neuroprotective action of avocado oil, reversing the induced mortality rates and also decreasing the events of oxidative stress and apoptosis induced by exposure to cortisol.